Thickness Optimization and Photovoltaic Properties of Bulk Heterojunction Solar Cells Based on PFB–PCBM Layer - Sayed Izaz Uddin (Energies, 2020)
We report on the fabrication and study of bulk heterojunction (BHJ) solar cells based on a novel combination of a donor–acceptor poly(9,9-dioctylfluorenyl-2,7-diyl)-co-(N,N0-diphenyl)-N,N′di(p-butyl-oxy-pheyl)-1,4-diamino-benzene) (PFB) and [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) blend composed of 1:1 by volume. indium tin oxide (ITO)/poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate (PEDOT:PSS)/PFB–PCBM/Ag BHJ solar cells are fabricated by a facile cost-effective spin-coating technique. The thickness of the active film (PFB–PCBM) plays an important role in the efficiency of light absorption, exciton creation, and dissociation into free charges that results in higher power conversion efficiency (PCE). In order to optimize the PCE as a function of active layer thickness, a number of solar cells are fabricated with different thicknesses of PFB–PCBM films at 120, 140, 160, 180, and 200 nm, and their photovoltaic characteristics are investigated. It is observed that the device with a 180 nm thick film demonstrates a maximum PCE of 2.9% with a fill factor (FF) of 53% under standard testing conditions (STC) (25 °C, 1.5 AM global, and 100 mW/cm2). The current–voltage (I-V) properties of the ITO/PEDOT:PSS/PFB–PCBM/Ag BHJ devices are also measured in dark conditions to measure and understand different parameters of the heterojunction. Atomic force microscopy (AFM) and ultraviolet-visible (UV-vis) absorption spectroscopy for the PFB–PCBM film of optimal thickness (180 nm) are carried out to understand the effect of surface morphology on the PCE and bandgap of the blend, respectively. The AFM micrographs show a slightly non-uniform and rough surface with an average surface roughness (Ra) of 29.2 nm. The UV-vis measurements of the PFB–PCBM blend exhibit a reduced optical bandgap of ≈2.34 eV as compared to that of pristine PFB (2.88 eV), which results in an improved absorption of light and excitons generation. The obtained results for the ITO/PEDOT:PSS/PFB–PCBM (180 nm)/Ag BHJ device are compared with the ones previously reported for the P3HT–PCBM blend with the same film thickness. It is observed that the PFB–PCBM-based BHJ device has shown two times higher open circuit voltage (Voc) and, hence, enhanced the efficiency.